Pengukuran Usability System Terhadap Aplikasi Gojek dengan Use Questionnaire - Hartati, Eka (Teknomatika, 2017)
Gojek application is used to provide gojek services for gojek user that consists of the menu go-ride, go-send, go-mart, food, go-go-go-box, clean, go-glam-massage, go, go-busway, and go-tix and can be accessed through (www.go-jek.com). This research aims to do usability measurement system against gojek application for the user gojek in Palembang. Components of usability in this study consisted of learnability, memorability, error, efficienci, and satisfaction with the use of measuring instrument use quesionairre, which has an ordinal data type, and shape measurement using likert scale scale with 159 respondents. The value of usability above average 2.50 so that it can be said that the application of good and gojek can be accepted and used by all people.Keywords: Application Gojek, Usability, Use Quesionairre.